Impact of the "We Race As One" campaign in the manufacturing unit of British American Tobacco Bangladesh - Nafis, Sadman (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.